Hubungan Berat Badan Berlebih dengan Kejadian Sindrom Syok Dengue pada Anak yang Dirawat dengan Demam Berdarah Denguedi RSUP Dr. M. Djamil Padang - Aliffia Luthfiyyana; Dian Pertiwi; Amirah Zatil Izzah; Desmawati Desmawati; Tuti Handayani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Dengue hemorrhagic fever (DHF) is one of the highest causes of death due to infection in Indonesia. The death rate will increase if dengue infection develops into dengue shock syndrome (DSS). Children tend to experience DHF and even DSS because their capillary permeability is higher than adults. Being overweight is a risk factor that increases a person's chances of experiencing DSS due to a strong immune response, which causes increased production of pro-inflammatory cytokines. This research aims to determine the relationship between overweight and the incidence of DSS in children. This research was an observational analytical study with the cross-sectional design. Sampling was done by a total sampling technique in pediatric patients treated for dengue hemorrhagic fever at Dr. M. Djamil Padang Hospital for the period 1 January 2018 – 31 December 2021. The data was obtained from the medical records of Dr. M. Djamil Padang Hospital between November 2023 to January 2024 with a total of 179 sample of DHF children aged 0 – 18 years. Chi-square test was used as statistical test. The results of this research were that DSS cases occurred more frequently in the 5 - 10 year age group (33,5%) with female gender (33%). Most of the sampel had good nutritional status, the most common degree of infection was grade III, duration of fever for 4 – 6 days, and good outcome. Bivariate analysis with the chi-square test obtained a p value of 0.007 (p<0.05). This research is concluded that there is a statistically significant relationship between overweight and the incidence of DSS in children treated for DHF at Dr. M. Djamil Padang Hospital.